An External Focus of Attention Enhances Manual Tracking of Occluded and Visible Targets - Schlesinger, Matthew; Porter, Jared; Russell, Robert (Frontiers in Psychology, 2013)
The present study investigated the enhancement effects of an external focus-of-attention (FOA) in the context of a manual-tracking task, in which participants tracked both visible and occluded targets. Three conditions were compared, which manipulated the distance of the FOA from the participant as well as the external/internal dimension. As expected, an external FOA resulted in lower tracking errors than an internal FOA. In addition, analyses of participants' movement patterns revealed a systematic shift toward higher-frequency movements in the external FOA condition, consistent with the idea that an external FOA exploits the natural movement dynamics available during skilled action. Finally, target visibility did not influence the effect of focused attention on tracking performance, which provides evidence for the proposal that the mechanisms that underlie FOA do not depend directly on vision.